Farm Broadcaster Knowledge and Beliefs of Biotechnology and Genetically Modified Organisms - David L. Doerfert; J. Tanner Robertson; Cindy Akers; Mark Kistler (Journal of Applied Communications, 2005)
Farm broadcasting members of the National Association of Farm Broadcasters (NAFB) were studied to determine their knowledge and beliefs about biotechnology and genetically modified organisms. This study used bimodal data collection techniques. Farm broadcasters in this study were described as typically male, over 35 years of age, married, and with at least some college education. Most farm broadcasters had an audience size of more than 50,000 listeners with typically a local distribution. In addition, most deliver a story about biotechnology and genetically modified organisms at least once a week. The majority of farm broadcasters believed that it was important to have a knowledge base of the subject they were reporting on, yet they did not demonstrate a high level of knowledge about food biotechnology, as measured by eight multiple choice questions. The average farm broadcaster only answered five of the eight questions correctly. Farm broadcasters believe that the U.S. food supply is safe and do not feel that GMOs are a risk for future generations. However, farm broadcasters believe that their audiences have a higher perception of GMOs as a potential risk to future generations. Recommendations for future research and evaluation of university agricultural communication curriculum are included.